Transforming political advertising in Malaysia: strategizing political advertisements towards first-time and young voters in Malaysian GE 14 - Mohd Helmi Abd Rahim,; Novel Lyndon,; Nazrin Shahnaz Peer Mohamed, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Undoubtedly, the 2013 Malaysia’s general election campaign marked to have significantly increased in budget, and much was contributed to advertising. The general election 2013 was noted to be among the most interesting campaign, with salient competitive campaign among the two coalition political parties. This research aims at analyzing the 2013 political advertisements rendered during the time, in order to give insights as to transform and strategize the next 2018 General Election advertising campaign. The king-makers are to be the first-time and young voters. The study approach to understand the effectiveness of political advertising during the general election campaign 2013 to the first- time voters; on how they perceived the advertisements, whether those advertisements have an impact on them, and their preferred advertisements content, elements, and style that suited the first- time voters, and, hence drew the most likeability and believability to the changes of perspectives of these first-time voters after a period of 4 years. The research employs the focus group method. This method was chosen as it allows access to socially-constructed expressed views, opinions, experiences, and attitudes as the respondents interpreted the advertisements messages and elements. Eighteen participants were identified to form three different groups representing the rural, semi-urban and urban first- time voters. The results show that there are many elements that were not acknowledged by the creators of advertisements and the political parties as to design and strategizing their campaign. There is a lack of effectiveness in persuasion and communicating through advertisement, to the first-time voters. Though political messages remain unpopular, but it plays a rather significant role in influencing the young voters’ to vote in the coming election. Suggestions are made on transforming the political advertisements as to improve effectiveness in the coming Malaysian General Election.